The cellular characterization of SARS-CoV-2 spike protein in virus-infected cells using the receptor binding domain binding specific human monoclonal antibodies - Chan, Conrad En-Zuo (2022)
A human monoclonal antibody panel (PD4, PD5, PD7, SC23, and SC29) was isolated from the B cells of convalescent patients and used to examine the S protein in SARS-CoV-2-infected cells. While all five antibodies bound conformational-specific epitopes within SARS-CoV-2 spike (S) protein, only PD5, PD7, and SC23 were able to bind to the receptor binding domain (RBD). Immunofluorescence microscopy was used to examine the S protein RBD in cells infected with the Singapore isolates SARS-CoV-2/0334 and SARS-CoV-2/1302. The RBD-binders exhibited a distinct cytoplasmic staining pattern that was primarily localized within the Golgi complex and was distinct from the diffuse cytoplasmic staining pattern exhibited by the non-RBD-binders (PD4 and SC29). These data indicated that the S protein adopted a conformation in the Golgi complex that enabled the RBD recognition by the RBD-binders. The RBD-binders also recognized the uncleaved S protein, indicating that S protein cleavage was not required for RBD recognition. Electron microscopy indicated high levels of cell-associated virus particles, and multiple cycle virus infection using RBD-binder staining provided evidence for direct cell-to-cell transmission for both isolates. Although similar levels of RBD-binder staining were demonstrated for each isolate, SARS-CoV-2/1302 exhibited slower rates of cell-to-cell transmission. These data suggest that a conformational change in the S protein occurs during its transit through the Golgi complex that enables RBD recognition by the RBD-binders and suggests that these antibodies can be used to monitor S protein RBD formation during the early stages of infection. IMPORTANCE: The SARS-CoV-2 spike (S) protein receptor binding domain (RBD) mediates the attachment of SARS-CoV-2 to the host cell. This interaction plays an essential role in initiating virus infection, and the S protein RBD is therefore a focus of therapeutic and vaccine interventions. However, new virus variants have emerged with altered biological properties in the RBD that can potentially negate these interventions. Therefore, an improved understanding of the biological properties of the RBD in virus-infected cells may offer future therapeutic strategies to mitigate SARS- CoV-2 infection. We used physiologically relevant antibodies that were isolated from the B cells of convalescent COVID-19 patients to monitor the RBD in cells infected with SARS-CoV-2 clinical isolates. These immunological reagents specifically recognize the correctly folded RBD and were used to monitor the appearance of the RBD in SARS-CoV-2-infected cells and identified the site where the RBD first appears.